2008
DOI: 10.1063/1.2829810
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from Mo2C coated carbon nanosheets

Abstract: Carbon nanosheets have recently evolved into useful edge emitters with high emission current densities, low threshold electric fields, and long lifetimes. In addition to further improvement in these characteristics, good stability and repeatability are also essential for these materials to be suitable for high vacuum applications such as microwave tubes and flat panel displays. Since the work function of graphite, carbon nanotubes, and amorphous carbon is relatively high, 4.6-4.8 eV, selective thin film coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…7). This can be explained by the fact that edges of the as-deposited CNS are H-terminated [15,16] since the deposition is carried out in a methane/hydrogen atmosphere. These H-terminated edges are not very reactive adsorption sites.…”
Section: Article In Pressmentioning
confidence: 97%
“…7). This can be explained by the fact that edges of the as-deposited CNS are H-terminated [15,16] since the deposition is carried out in a methane/hydrogen atmosphere. These H-terminated edges are not very reactive adsorption sites.…”
Section: Article In Pressmentioning
confidence: 97%
“…Using the standard Fowler-Nordheim theory, the field enhancement factor, ␤, can be calculated from the slope and gives ␤ ϳ 1320, and is consistent with previous analysis of CNS samples. 30 The linear least mean square fits of RGA data as a function of current are shown in Fig. 6 with 95% confidence bounds as an indication of the spread in the data.…”
Section: Methodsmentioning
confidence: 99%
“…The sheets are consisting of several graphene layers and stand roughly vertical to the substrate. It has been found that CNSs have good field emission characteristics with promising applications in vacuum microelectronic devices [3,4,5,6]. High emission total current at low threshold field enables using CNSs as an effective cold cathode material.…”
mentioning
confidence: 99%